2021
DOI: 10.3390/cancers13236106
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-Releasing Peptide Receptor Antagonist [68Ga]RM2 PET/CT for Staging of Pre-Treated, Metastasized Breast Cancer

Abstract: Background: Positron emission tomography (PET)/computed tomography (CT) using the gastrin-releasing peptide receptor antagonist [68Ga]RM2 has shown to be a promising imaging method for primary breast cancer (BC) with positive estrogen receptor (ER) status. This study assessed tumor visualization by [68Ga]RM2 PET/CT in patients with pre-treated ER-positive BC and suspected metastases. Methods: This retrospective pilot study included eight female patients with initial ER-positive, pre-treated BC who underwent [6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…GRPR is one of the most commonly overexpressed receptors in prostate ( 5 , 6 ), breast ( 7 ) and lung cancer ( 8 ). And GRPR mediates the transmission of non-histaminergic itch in the dorsal horn of the spinal cord ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRPR is one of the most commonly overexpressed receptors in prostate ( 5 , 6 ), breast ( 7 ) and lung cancer ( 8 ). And GRPR mediates the transmission of non-histaminergic itch in the dorsal horn of the spinal cord ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are widely distributed in the central nerve system (CNS) and peripheral tissues with extensive effects on the physiological and pathological processes ( 4 ). Mammalian BBN receptors, especially GRPR, are of particular interest in oncology as their high expression in several human cancers, such as the prostate ( 5 , 6 ), breast ( 7 ), and small-cell lung cancers ( 8 ), as well as in the CNS/neural tumors including gliomas, neuroblastomas, and medulloblastomas ( 9 ). BBN is a 14-residue peptide (Pyr-QRLGNQWAVGHLM-NH 2 ) first isolated from the skin of the European fire-bellied toad Bombina bombina and its mammalian counterpart gastrin-releasing peptide (GRP), a 27-residue peptide, shares the same C terminus of Trp-Ala-Val-Gly-His-Leu-Met-NH 2 with BBN ( 10 ).…”
mentioning
confidence: 99%
“…Of note, Michalski et al reported two of two ER-positive metastatic ILC patients negative on GRPR PET. [ 24 ] Both patients reported current endocrine therapy for a duration of at least 18 months and one of two patients subsequently had loss of ER expression on examination of metastatic breast cancer cells. In our study, neither patient with ILC was on endocrine therapy at the time of imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a new study from the same group ( 215 ) on eight female patients with initial ER+ BC, demonstrated how [ 68 Ga]Ga-RM2 PET/CT could support treatment decisions in these patients, guide radiotherapy planning in oligometastatic patients or select patients for RM2 radioligand therapy.…”
Section: Gastrin-releasing Peptide Receptor Targeted Radiotracersmentioning
confidence: 99%